EFFECTS OF ZINC AND SALICYLIC ACID ON WHEAT UNDER DROUGHT STRESS - I. Yavas; A. Unay (Journal of Animal and Plant Sciences, 2016)
The present study was conducted to investigate whether exogenous application of salicylic acid (SA) and zinc (Zn) could regulate the activities of antioxidant enzymes and ameliorate the adverse effects of drought stress on wheat. Pot experiment was arranged in a Randomized Complete Block Design (RCBD) with two factors and three replications during the year 2013-2014 in Turkey. The control, drought, drought + SA and drought + Zn were first factor, and the wheat cultivars, Basribey and Ziyabey 98, were second factor. Drought stress at grain filling stage significantly decreased plant height, spike length, number of grains per spike, 1000 grain weight, chlorophyll content, relative water content but activity of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) under drought stress were increased. Both SA and Zn application had positive influence on all parameters in this experiment. The foliar application of Zn increased water use efficiency and thereby reduced the negative effects of drought stress. Besides the foliar application of salicylic acid regulated physiological processes in plants and alleviated the adverse effects of water stress. Results showed that SA and Zn could be used for improving wheat growth under drought stress.
Keywords: Antioxidant enzyme activity; Drought stress; Foliar application; Salicylic acid; Zinc